EMPLOYING THE MORAL INTELLIGENCE OF LEADERS TO REDUCE ADMINISTRATIVE AND FINANCIAL CORRUPTION: AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF WORKERS IN THE DIRECTORATE OF MUNICIPALITIES OF MUTHANNA GOVERNORATE - Sadeq Mahdi Shliot; Ahmed Ghorbel (Galaxy International Interdisciplinary Research Journal, 2024)
This study aims to analyze the impact of employing the moral intelligence of leaders in reducing administrative and financial corruption through an analytical study of the opinions of a sample of employees in the Directorate of Municipalities of Muthanna Governorate. The study investigates the dimensions of leaders’ moral intelligence and its relationship to reducing corruption, as well as the influence of leaders’ ethical qualities on the level of transparency and integrity in public institutions.